Liability for Medical Negligence: A study of Islamic Law (Al-Qamar, 2019)
Preservation of life is one of the five main objectives of Sharī‘ah. Preservation of life includes preservation of health too. Every human being falls ill at some point of life and needs assistance of medical practitioner. Medicine is an inexact science and can go wrong. In such cases of mistake, misadventure, negligence and criminal actions, doctors and patients end up in court of law.  It is pertinent for Muslim doctors, patients and courts to seek the knowledge about the perspective of Sharī‘ah regarding practice of medicine. Sharī‘ah guides medical practitioners by providing them general principles for the practice of medicine and enlightens the patients about their rights. Furthermore, it directs the courts and doctors about their liability. Medical malpractice law in Sharī‘ah started with the tradition of Prophet: “He who sets himself up, and undertakes the treatment of others, but had not prepared himself well for medical practice and as result has caused harm, is liable.” This tradition and many other guidelines from Quran and Sunnah formed the basis of Islamic Law of medical practice. Muslim Jurists (fuqahā) expounded these concepts and guided medical practitioners about their liabilities in cases of misadventures, mistakes and negligence. This article aims at exploring the treasure of Sharī‘ah regarding the liability of medical practitioners. It argues that Sharī‘ah incurs the liability to compensate for the harm caused due to negligence and mistake while criminal liability is invoked only in the cases of gross negligence.
Keywords: Sharī‘ah; Medicine; Doctors; Negligence; liability